Kringles of substrate plasminogen provide a 'catalytic switch' in plasminogen to plasmin turnover by Streptokinase. Issue 5 (6th March 2020) - Sharma, Vandna; Kumar, Shekhar; Sahni, Girish
Abstract : To understand the role of substrate plasminogen kringles in its differential catalytic processing by the streptokinase — human plasmin (SK-HPN) activator enzyme, Fluorescence Resonance Energy Transfer (FRET) model was generated between the donor labeled activator enzyme and the acceptor labeled substrate plasminogen (for both kringle rich Lys plasminogen — LysPG, and kringle less microplasminogen — µPG as substrates). Different steps of plasminogen to plasmin catalysis i.e. substrate plasminogen docking to scissile peptide bond cleavage, chemical transformation into proteolytically active product, and the decoupling of the nascent product from the SK-HPN activator enzyme were segregated selectively using (1) FRET signal as a proximity sensor to score the interactions between the substrate and the activator during the cycle of catalysis, (2) active site titration studies and (3) kinetics of peptide bond cleavage in the substrate. Remarkably, active site titration studies and the kinetics of peptide bond cleavage have shown that post docking chemical transformation of the substrate into the product is independent of kringles adjacent to the catalytic domain (CD). Stopped-flow based rapid mixing experiments for kringle rich and kringle less substrate plasminogen derivatives under substrate saturating and single cycle turnover conditions have shown that the presence of kringle domains adjacent to the CD in the macromolecular substrate contributes by selectively speeding up the final step, namely the product release/expulsion step of catalysis by the streptokinase-plasmin(ogen) activator enzyme.